2020
DOI: 10.1002/eat.23385
|View full text |Cite
|
Sign up to set email alerts
|

The COVID‐19 pandemic: Psychological and behavioral responses to the shutdown of the beauty industry

Abstract: Objective: During the COVID-19 pandemic, Australia implemented widespread closure of beauty and cosmetic services to control the virus spread. The effect of these restrictions is unknown, given that beauty services are widely used for stress relief or to enhance confidence. The current study explored the relationship between engagement in appearance-focused behaviors and distress regarding beauty service closure. Participants with high and low levels of dysmorphic concern were compared to determine whether COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 44 publications
0
60
1
1
Order By: Relevance
“…First of all, the extended duration of lockdown and stay‐at‐home policies might have caused visible and frequent facial lesions such as acne, rosacea, comedones, and melasma to draw greater attention. Accordingly, a recent report showed an increase in appearance‐focused behaviors (eg, mirror checking, appearance comparisons) in patients with higher dysmorphic concern during the COVID‐19 pandemic due to the closure of beauty services 33 . Moreover, another study reported an association between COVID‐19‐related stress negative body image in adults 34 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…First of all, the extended duration of lockdown and stay‐at‐home policies might have caused visible and frequent facial lesions such as acne, rosacea, comedones, and melasma to draw greater attention. Accordingly, a recent report showed an increase in appearance‐focused behaviors (eg, mirror checking, appearance comparisons) in patients with higher dysmorphic concern during the COVID‐19 pandemic due to the closure of beauty services 33 . Moreover, another study reported an association between COVID‐19‐related stress negative body image in adults 34 .…”
Section: Discussionmentioning
confidence: 97%
“…13 Another finding of this study was the initially decreased interest in "comedones, acne, melasma, rosacea, Botox, Dermaroller, peeling, showed an increase in appearance-focused behaviors (eg, mirror checking, appearance comparisons) in patients with higher dysmorphic concern during the COVID-19 pandemic due to the closure of beauty services. 33 Moreover, another study reported an association between COVID-19-related stress negative body image in adults. 34 The subsequent increase of interest in cosmetic procedures such as botulinum toxin injections, dermaroller, and chemical peeling may also be explained by these findings.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 high-speed radio waves must be used to observe individual and social health problems that may cause them to stay home at social distances. [21][22][23] These issues have a direct impact on consumer behavior in online shopping. 24 The recent spread of AR and VR applications that utilize smartphone technology has increased with the universalization of smartphone adoption.…”
Section: Discussionmentioning
confidence: 99%
“…This increment in Chile could be happened due to the lockdown (150 days) restriction which had seen to cause the sleeping problem, screen exposure, and disruption in behavioral appearance. 1,2 Of all Americas countries, the USA was hit hard by most COVID-19 cases and deaths (WHO). This surge of cases caused a huge impact on the healthcare system in the USA such as in diabetics to care, substantial racial and ethnic disparities, and cognitive heart failure, etc.…”
Section: Discussionmentioning
confidence: 99%
“…1 People of dysmorphic concern usually went to Beaty Service for improving their behavioral appearance through engagement and practice are now having higher dysmorphic concern for “Stay Home” order. 2 In addition, dermatitis patients who have skin problems like hair and scalp diseases usually needed to take treatment from hospitals now also suffering from this situation. 3…”
Section: Introductionmentioning
confidence: 99%